Substrate integrated waveguide monopolar ring‐slot antenna. Issue 8 (August 2014) - Lacik, Jaroslav; Mikulasek, Tomas; Raida, Zbynek; Urbanec, Tomas
ABSTRACT A single‐layer substrate integrated waveguide (SIW) monopolar ring‐slot antenna is proposed in this letter. It is based on a combination of a circular ring‐slot etched in the SIW top wall and a set of shorting vias placed concentrically between the area bounded by the ring and the SIW bottom wall. Thanks to this configuration, a monopole‐like radiation pattern is obtained. The antenna is designed for the 5.8 ISM frequency band, parametrically studied and experimentally verified in free space and in the vicinity of a muscle‐equivalent phantom. Experimental results prove that the antenna is very well matched in the 5.8 GHz ISM band, has good radiation performance and small sensitivity to the surrounding environment. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1865–1869, 2014